New insights and advances of sodium-glucose cotransporter 2 inhibitors in heart failure - Juexing Li; Juexing Li; Lei Zhou; Lei Zhou; Hui Gong; Hui Gong (Frontiers in Cardiovascular Medicine, 2022)
Sodium-glucose cotransporter 2 inhibitors (SGLT2is) are newly emerging insulin-independent anti-hyperglycemic agents that work independently of β-cells. Quite a few large-scale clinical trials have proven the cardiovascular protective function of SGLT2is in both diabetic and non-diabetic patients. By searching all relevant terms related to our topics over the previous 3 years, including all the names of agents and their brands in PubMed, here we review the mechanisms underlying the improvement of heart failure. We also discuss the interaction of various mechanisms proposed by diverse works of literature, including corresponding and opposing viewpoints to support each subtopic. The regulation of diuresis, sodium excretion, weight loss, better blood pressure control, stimulation of hematocrit and erythropoietin, metabolism remodeling, protection from structural dysregulation, and other potential mechanisms of SGLT2i contributing to heart failure improvement have all been discussed in this manuscript. Although some remain debatable or even contradictory, those newly emerging agents hold great promise for the future in cardiology-related therapies, and more research needs to be conducted to confirm their functionality, particularly in metabolism, Na+-H+ exchange protein, and myeloid angiogenic cells.